Intervention effects of traditional Chinese medicine on stem cell therapy of myocardial infarction - Wang, Yu; Xue, Yuezhen; Guo, Hai-dong (Frontiers in Pharmacology, 2022)
Cardiovascular diseases are the leading cause of global mortality, in which myocardial infarction accounts for 46% of total deaths. Stem cell therapy on damaged myocardial repair has evolved into a promising treatment for ischemic heart disease. However, low retention and poor survival of the transplanted stem cells are major obstacles to achieving the intended therapeutic effects. Chinese herbal medicine is a rich source of effective treatment for various diseases. As such, numerous studies have revealed the promoting role of Chinese medicine in stem cell therapy for myocardial infarction treatment, including optimizing the microenvironment and promoting proliferation, survival, migration, and differentiation of stem cells. Here, we discuss the potential and limitations of stem cell therapy, as well as the regulatory mechanism of Chinese medicines underlying stem cell therapy. We focus on the evidence made from pre-clinical trials and clinical practice and summarize the theoretical basis for the efficacy of traditional Chinese medicine from the perspective of stem cells.